Pelatihan Pengembangan Permainan Kecil sebagai Persiapan Pengenalan Lapangan Persekolah (PLP) Calon Guru Penjas - Nur Synthiawati, Novita; Budi Prasetyo, Guntum; Prasetiyo, Rahayu; Yunarta, Arsika (Community Education Engagement Journal, 2024)
Based on the purpose of this service, it provides knowledge and skills in small games in PJOK for physical education students who will carry out PLP in schools, so that later students apply skills in small games creatively and innovatively in every lesson and the methods in this activity used are lectures and questions and answers, demonstrations and practices. In the implementation of this activity by conveying explanations related to small games and forms of exercise with practice in the field. Evaluation summarises events in activities related to the situation and input for these activities, the results of the activity that students gain understanding related to making various modifications and making creations in small games for that prospective PE teacher students at PGRI Jombang University must always be creative in making fun learning materials according to the development of their students.